2016
DOI: 10.17221/63/2015-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Immunological attributes of blood and milk neutrophils isolated from crossbred cows during different physiological conditions

Abstract: ABSTRACT:The goal of this work was to understand how polymorphonuclear leukocytes (PMN), the first line of cellular defence, integrate and prioritize multiple chemotactic signals to navigate during periods of demand like subclinical mastitis (SCM), clinical mastitis (CM), pregnancy (P), and calving (C). For this, blood and milk samples were collected from five groups of crossbred cows (healthy, with SCM, CM, pregnant, and newly calved). Maximum viability was seen in the PMN of healthy cows, whereas minimum via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
1
21
2
Order By: Relevance
“…It has been found that IL‐8 is released in response to cell stressors such as reactive oxygen species, bacterial fragments and proinflammatory cytokines (DeForge et al., ). Increased IL‐8 expression has also been observed in the blood neutrophils of calving cows with clinical mastitis (Alhussien et al., ). A positive relationship between IL‐8 gene expression and the incidence of severe mastitis has also been found (Galvao, Pighetti, Cheong, Nydam, & Gilbert, ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been found that IL‐8 is released in response to cell stressors such as reactive oxygen species, bacterial fragments and proinflammatory cytokines (DeForge et al., ). Increased IL‐8 expression has also been observed in the blood neutrophils of calving cows with clinical mastitis (Alhussien et al., ). A positive relationship between IL‐8 gene expression and the incidence of severe mastitis has also been found (Galvao, Pighetti, Cheong, Nydam, & Gilbert, ).…”
Section: Resultsmentioning
confidence: 96%
“…Chemokines regulate the migration and adhesion of infiltrating cells to an inflamed lesion (Nedoszytko, Sokołowska‐Wojdyło, Ruckemann‐Dziurdzińska, Roszkiewicz, & Nowickiù, ). Resident tissue cells, such as macrophages and neutrophils, express several chemokines (Alhussien et al., ; Rossi & Zlotnik, ). In our study, IL‐8 transcript accumulation was reduced in both macrophages (Figure ) and neutrophils (Figure ), but the results were not significant.…”
Section: Resultsmentioning
confidence: 99%
“…SCC variation has been noted between various breeds of cows [ 14 , 22 , 27 , 56 - 58 ] as presented in Figure-3 . The high-producing cattle breeds such as Brown Swiss and Holstein have a higher presence of SCC/ml in milk.…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%
“…Average SCC for 212 dairy herds was found to be around 241,000±83,000 cells per ml [ 42 ]. It has been found that indigenous cow breeds like Tharparkar have less milk SCC as compared to Karan Fries cows [ 14 , 22 ]. Breed type also influences the shape of udder, and teats with well-attached udders show less incidence of mastitis than pendulous-shaped udder [ 15 , 59 ].…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%
See 1 more Smart Citation